May Dyspnea Sensation Influence the Sexual Function in Men With Obstructive Sleep Apnea Syndrome? A Prospective Control Study. Issue 3 (18th July 2019) - Skoczyński, Szymon; Nowosielski, Krzysztof; Minarowski, Łukasz; Brożek, Grzegorz; Oraczewska, Aleksandra; Glinka, Klaudia; Ficek, Karolina; Kotulska, Beata; Tobiczyk, Ewelina; Skomro, Robert; Mróz, Robert; Barczyk, Adam
Abstract: Introduction: Dyspnea sensation is frequently present in obstructive sleep apnea syndrome (OSA) patients; however, its possible influence on sexual function and body image has not been well analyzed. Aims: To evaluate sexual function, the prevalence of sexual dysfunction (SD), and body image during sexual activity and its relationship with dyspnea in men with OSA. Methods: 129 men were included in the prospective study, with 61 diagnosed with OSA (cases) and 68 age- and BMI-matched healthy control subjects. Patients were assessed for the severity of heart failure by the New York Heart Association scale and dyspnea by the Visual Analogue Scale. OSA was confirmed by in-laboratory polysomnography. Main Outcome Measures: International Index of Erectile Function (IIEF) was used as a measure of sexual function, body image during sexual activity was assessed by the Body Exposure During Sexual Activity Questionnaire, whereas SD was diagnosed using criteria from the Diagnostic and Statistical Manual of Mental Disorders, 5th edition. Results: The mean age of the studied population was 57.9 ± 10.8 years. Presence of dyspnea interfered with sexual life in 20% of men diagnosed with OSA and with work performance in 33%. Men with OSA had worse scores in IIEF-15 compared with control subjects and higher frequency of sexual distress compared with men with OSA. There were no differences in the rate of SD according to criteria from the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition. The presence of OSA worsened the perceived body image during sexual activity. The presence of dyspnea was the only negative factor affecting sexual function in general (IIEF-15 score) and 1 of the factors affecting erectile function and orgasmic function. Conclusion: In men with OSA, body image is negatively influenced by the presence of OSA. Furthermore, the presence of dyspnea assessed by the New York Heart Association scale impairs sexual function in that group of men.